Validation of the megakaryocyte fragmentation theory of finger clubbing in patients with cardiopulmonary diseases. (August 2014) - Arivazhagan, Srinivasan; Kadhiravan, Tamilarasu; Basu, Debdatta; Dutta, Tarun Kumar
Abstract Dickinson and Martin had proposed that finger clubbing is caused by distal impaction of large-sized platelets that escape physiological fragmentation in lung vasculature. Empirical evidence to support this theory, however, is limited and conflicting. Moreover, this theory has not been verified in patients with lung diseases. We conducted a cross-sectional analytic study to validate the megakaryocyte fragmentation theory in patients with cardiopulmonary diseases. We studied four groups – patients with cyanotic heart diseases and clubbing (n = 20); patients with non-malignant lung diseases and clubbing (n = 25); patients with non-malignant lung diseases but no clubbing (n = 25); and healthy individuals (n = 25). We measured the distal phalangeal depth ratio, estimated the platelet volume indices, and examined the peripheral blood smear for the presence of large platelets. We found that patients with clubbing due to cyanotic heart diseases had a significantly lower platelet count (median [IQR] 201 [157–241] vs. 303 [258–334] × 103/μl; p < 0.001), higher platelet volume (mean difference, Δ [95% CI] = 0.93 fl [0.37–1.49 fl]; p = 0.002) and platelet large cell ratio (Δ = 7.99% [3.71%–12.26%]; p < 0.001) as compared to healthy individuals. They were also significantly more likely to have large platelets on peripheral blood smear as compared to healthy individuals (9/25 vs. 0/25; p = 0.002). However, in patients with lung diseases, irrespective of the presence or absence of clubbing, platelet count and platelet volume indices were not different from healthy individuals. Our findings support the megakaryocyte fragmentation theory of finger clubbing in patients with cyanotic heart diseases. However, this theory does not explain the clubbing seen in non-malignant lung diseases.